Knowledge, confidence, attitudes and beliefs of physiotherapists and physiotherapy students working with people with dementia: A mixed‐methods systematic review. (December 2021) - Quick, Stephen; Snowdon, David A; Lawler, Katherine; McGinley, Jennifer; Soh, Sze Ee; Callisaya, Michele L
Abstract: Background: Clinical care for people with dementia as a primary diagnosis, or as a co‐morbidity, can be complex. Physiotherapists play a key role in the care of people living with dementia in multiple settings. The aim of this systematic review is to understand the attitudes, beliefs, knowledge and confidence of physiotherapists and physiotherapy students when working with people with dementia. Method: This was a mixed‐methods systematic review that included qualitative and quantitative studies. Participants were physiotherapists working in any clinical specialty (e.g. gerontology, orthopaedic, neurological, cardio‐respiratory), and physiotherapy students who had completed at least one clinical placement. If studies investigated physiotherapist and physiotherapy students' knowledge, confidence, attitudes or beliefs on working with a general population of older adults, they were excluded. The phenomena of interest and context were attitudes, beliefs, knowledge and confidence when working with people with dementia in any setting. Eleven databases were searched. Data synthesis followed a convergent integrated approach according to Joanna Briggs Institute methodology for mixed methods systematic reviews. Result: 15 studies were eligible for inclusion (9 quantitative and 6 qualitative studies). There were 5 key themes: rehabilitation potential (variable outcomes, poor potential), challenges in dementia care (communication, behaviour, cognition, risk, stress and burnout), education in dementia practice (inadequate training and knowledge, importance of experience), specialised area of practice (complexity of presentation, nuance of care, importance of time, holistic approach) and unsupportive systems (environment, time, risk aversion). One code, lack of desire to provide dementia care, did not contribute to any themes. Conclusion: Physiotherapists and physiotherapy students have low levels of knowledge and confidence in several areas important to working with people with dementia. With higher levels of knowledge and confidence associated with more positive attitudes and beliefs, dementia education needs of physiotherapists at all levels needs to be addressed.